Validation of the nutrient-rich foods index estimated by 24-h dietary recall method among adults in Henan province of China - Zhai, Junya; Ma, Baihui; Lyu, Quanjun; Guo, Lijun; Khatun, Pipasha; Liang, Rui; Cong, Minghua; Kong, Yongxia (Public health nutrition, 2022)
A family of nutrient-rich food (NRF) indices was validated against the mean adequacy ratio (MAR) and their associations with obesity were tested. Cross-sectional study. NRF indices include nutrients to encourage ranging from 6-11 (protein; fibre; vitamin A, vitamin C, vitamin E and vitamin B12; Ca; Fe; K; Mg; Zn) and two nutrients to limit (saturated fat and Na), described as NRFn.2 (where n 6-11), based on reference amount of 100 g or 100 kcal using the NRF index family of algorithms. The percentage of variation in MAR (R2) was the criteria of index performance. Logistic regression models were applied to predict the association between NRF index and obesity. Three communities in Zhengzhou city, Henan province, China. A total of 656 adults were recruited from Henan as the subjects. The NRF9·2 index, based on nine beneficial nutrients and two nutrients to limit, using the algorithm based on sums and 100 kcal, had the higher R2 values (R2 = 0·232). The OR for overweight (defined by BMI) in the 4th quartile (Q4) v. the 1st quartile (Q1) of the NRF9·2 index was 0·61 (95 % CI = 0·37, 0·98) after multiple adjustments. NRF9·2 index using the algorithm based on sums and 100 kcal gave the best predicted model for diet quality. NRF9·2 index score was associated with overweight defined by BMI, but it was not associated with central obesity. The NRF9·2 index is a valid tool to assess the overall diet quality among adults in Henan province of China.